UJI ORGANOLEPTIK DAN SIFAT KIMIA KUE SEMPRONG CAMPURAN TEPUNG UBI JALAR UNGU (IPOMOEA BATATAS) DAN TEPUNG TERIGU - Montolalu, Olfita S.; Langi, Tineke M.; Koapaha, Teltje (Fakultas Pertanian, Universitas Sam Ratulangi, 2020)
ABSTRACTThe aim of this research is to produce a quality semprong cookies by mixing purple sweet potato flour and flour properly, based on the panelists' preference level and the nutritional characteristics of the